Can small‐scale fisheries survive market‐based management? Nordic evidence. Issue 1 (27th September 2021) - Nielsen, Max; Andersen, Peder; Asche, Frank; Ellefsen, Hans; Hammarlund, Cecilia; Hoff, Ayoe; Kristofersson, Dadi Mar; Nielsen, Rasmus; Rógvi, Heri á; Roll, Kristin; Sævaldsson, Hordur; Virtanen, Jarno; et al.
Abstract: Market‐based fisheries management systems give incentives to reduce the fleet size and employment, which increases earnings and contributes to resolve the tragedy of the commons. However, the often‐stated expectation that economies of scale cause the disappearance of small‐scale fishery is not observed in many cases. In this study, we investigate the effects on fleet structure in the period after introducing individual fishing quotas or individual fishing days with various degrees of transferability in selected fisheries in the seven Nordic countries. Despite observing economies of scale in most cases, it is found that the market‐based fisheries management often does not reduce the small‐scale fleet more than the fleet of large vessels. This is explained partly by small vessels targeting demersal species and large vessels pelagic species, and partly by the larger need of larger than small vessels to continuously utilize their capital stocks through fast adaptation to ensure return. A more important explanation is the regulation design, with limitations in sale of fishing rights and lease between vessel groups and regions and in the share of the total quota holdings of fishing rights by individuals and vessels. This is important for countries considering the introduction of market‐based fisheries management, since the Nordic experiences show that with proper regulation design, economic gains can be achieved with small‐scale fishing surviving even under economies of scale.